The Implementation of E-Musrenbang Website to Increase Community Participation in Development Planning during Covid-19 Pandemic (Case Study of Glintung Water Street in Purwantoro Kota Malang) - Sekar Ayu Wandyra; Saiman Saiman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Regional development planning meetings (Musrenbang) are facilities that are facilitated by local governments to participate in regional development planning once a year. Community involvement is a very important element in the development process. The existence of technological advances that are currently developing does not prevent community participation in the musrenbang. E-Musrenbang is an application developed by the Regional Development Planning Agency (BAPEDDA) as part of the implementation of musrenbang activities. The purpose of this study is to analyze the application of community participation in development planning through the e-musrenbang website. This study uses a descriptive qualitative method. Data were collected through technical observation techniques on the people involved in the Tangguh Village development program. The results of this study are the use of e-musrenbang in planning Tangguh Village in Purwantoro Village is still not good, because the socialization carried out by the organizers has not been evenly distributed to the village level so that people do not understand and know the benefits of E-Musrenbang related to the proposals.